2010
DOI: 10.1111/j.1439-0426.2010.01448.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of prey composition for the condition of grey gurnard (Eutrigla gurnardus)

Abstract: During a fisheries research cruise on the Dogger Bank in the central North Sea, we studied the role of diet for the condition of grey gurnard (Eutrigla gurnardus). Seventeen stations across the Dogger Bank were sampled with the GOV otter trawl in April⁄May 2006. Each fish sampled was categorised according to three feeding types: a predator specialised on fish, on invertebrates or having a mixed diet, depending on the percentage of fish and⁄or invertebrates in the stomach. These predator-prey categories were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…7) might also reflect the difference in prey availability, although no evidence for this was observed; SCI during this period was lower in the northern area. The importance of prey utilization for the condition of predatory fishes has also been suggested for other demersal fishes such as Greenland halibut Reinhardtius hippoglossoides (Román et al 2007), Atlantic cod Gadus morhua (Pardoe et al 2008), bighand thornyhead Sebastolobus macrochir (Hattori et al 2009), and grey gurnard Eutrigla gurnardus (Weinert et al 2010).…”
Section: Discussionmentioning
confidence: 93%
“…7) might also reflect the difference in prey availability, although no evidence for this was observed; SCI during this period was lower in the northern area. The importance of prey utilization for the condition of predatory fishes has also been suggested for other demersal fishes such as Greenland halibut Reinhardtius hippoglossoides (Román et al 2007), Atlantic cod Gadus morhua (Pardoe et al 2008), bighand thornyhead Sebastolobus macrochir (Hattori et al 2009), and grey gurnard Eutrigla gurnardus (Weinert et al 2010).…”
Section: Discussionmentioning
confidence: 93%
“…Additionally, the differences in H. aduncum infection parameters between the localities may reflect the ecological characteristics of each. For example, differences between gurnard localities in the North Sea regarding the occurrence or abundance of preferred prey items (Weinert, Floeter, Kröncke, & Sell, 2010), which may also act as intermediate or transport hosts for H. aduncum, could significantly influence the infection level of this nematode species in Grey gurnard as well. From the present data, the differences in infection level between A. simplex and H. aduncum in both localities are not readily explained.…”
Section: General Aspectsmentioning
confidence: 99%
“…In the work by Weinert et al (2010), the highest HSI values were recorded for specimens with a mixed diet. All parasites of grey gurnard from the area of the Shetland Islands have complex life cycles and are passed passively through the food chain into the fish, which are the intermediate (paratenic) or definitive hosts.…”
Section: Discussionmentioning
confidence: 99%
“…The ratio of fish to invertebrates in gurnard stomachs can largely vary from year to year, and Kotterba (2008) reported that the average contribution of fish to the diet in the 25-30 cm length class was 72.8% and 20.2% in 1991 and 2007, respectively. Studies conducted by Weinert et al (2010) in the vicinity of the Dogger Bank in the central North Sea revealed that the amphipod Hyperia alba was the most abundant species found in gurnard stomachs, followed by Crangon allmani, and that the dominant vertebrates included the sandeel family (Ammodytidae) together with the species Ammodytes marinus. In the present study, the euphausiid Euphausia krohnii was the most abundant species, while poor cod Trisopterus minutus (Gadidae) dominated the vertebrates.…”
Section: Discussionmentioning
confidence: 99%